2016
DOI: 10.1021/acs.jmedchem.5b01998
|View full text |Cite
|
Sign up to set email alerts
|

Purine (N)-Methanocarba Nucleoside Derivatives Lacking an Exocyclic Amine as Selective A3 Adenosine Receptor Agonists

Abstract: Purine (N)-methanocarba-5′-N-alkyluronamidoriboside A3 adenosine receptor (A3AR) agonists lacking an exocyclic amine resulted from an unexpected reaction during a Sonogashira coupling and subsequent aminolysis. Because the initial C6-Me and C6-styryl derivatives had unexpectedly high A3AR affinity, other rigid nucleoside analogues lacking an exocyclic amine were prepared. Of these, the C6-Me-(2-phenylethynyl) and C2-(5-chlorothienylethynyl) analogues were particularly potent, with human A3AR Ki values of 6 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…The surprising finding that substitution of the exocylic NH of adenine with H or CH 3 in MRS5919 32 allowed full activation of the A 3 AR emphasized that the loss of otherwise important recognition elements in a ligand can be compensated by other affinity enhancing moieties on the nucleoside . Moreover, the ribose moiety is the main effector of receptor activation, while adenine modifications tend to change the subtype selectivity but usually do not have a major effect on the agonist efficacy.…”
Section: Medicinal Chemistry Of the A3 Adenosine Receptormentioning
confidence: 99%
See 1 more Smart Citation
“…The surprising finding that substitution of the exocylic NH of adenine with H or CH 3 in MRS5919 32 allowed full activation of the A 3 AR emphasized that the loss of otherwise important recognition elements in a ligand can be compensated by other affinity enhancing moieties on the nucleoside . Moreover, the ribose moiety is the main effector of receptor activation, while adenine modifications tend to change the subtype selectivity but usually do not have a major effect on the agonist efficacy.…”
Section: Medicinal Chemistry Of the A3 Adenosine Receptormentioning
confidence: 99%
“…133 The surprising finding that substitution of the exocylic NH of adenine with H or CH 3 in MRS5919 32 allowed full activation of the A 3 AR emphasized that the loss of otherwise important recognition elements in a ligand can be compensated by other affinity enhancing moieties on the nucleoside. 134 Moreover, the ribose moiety is the main effector of receptor activation, while adenine modifications tend to change the subtype selectivity but usually do not have a major effect on the agonist efficacy. However, there are exceptions to the above generalization, including various N 6 substituents and C2 substituents that produce partial agonism or antagonism at the A 3 AR, as has been summarized, 135 and nucleoside derivatives with reduced efficacy are discussed below.…”
Section: Adenosine Derivatives As Agonists Of the A 3 Adenosine Receptormentioning
confidence: 99%
“…The conformation adopted by FAD- A 3 AR complex revealed several interactions in the present model, and this is in good agreement with the data published previously. 34 , 35 Homology binding to other adenosine receptors was not as evident as with A 3 AR .…”
Section: Resultsmentioning
confidence: 90%
“…The same residue accepts a H-bond from the 6-amino group (bidentate ligand coordination). However, it was shown that a suitable combination of stabilizing interactions in these kind of hypermodified A 3 AR-selective ligands can partially compensate for the lack of an exocyclic amine, an otherwise important contributor to recognition in the A3AR binding site [32]. This is demonstrated by the sustained A3AR activity of MRS7195 and MRS7220 in cAMP signalling as well as in βarr2 recruitment (Table 2; Figure 2F; Figure 3, mustard curves), although MRS7220 has a substantially reduced Emax and logEC 50 compared to those of other (N)-methanocarba 5′-methyluronamide derivatives.…”
Section: Discussionmentioning
confidence: 99%